Case report: Excessive daytime sleepiness as a presenting manifestation of autoimmune glial fibrillary acidic protein astrocytopathy - Tang, Mingyang; Huang, Shuo; Guo, Weitong; Zhou, Junfang; Huang, Zhencan; Li, Wanru; Sun, Qingqing; Wang, Zan (Frontiers in Immunology, 2023)
Autoimmune glial fibrillary acidic protein astrocytopathy (GFAP-A) is a recently discovered autoimmune inflammatory disease of the central nervous system. It presents with a variety of clinical symptoms, including fever, seizures, psychiatric symptoms, limber weakness, and sensory symptoms. However, the symptoms of sleep disorders have not been sufficiently addressed. Here, we report a case of GFAP-A in which the patient complained of excessive daytime sleepiness and an excessive need for sleep. Our patient was a 58-year-old male who experienced excessive daytime sleepiness for 50 days following SARS-CoV-2 infection. He was diagnosed with coronavirus disease 2019 on June 1st. On the 7th of June, he experienced excessive daytime sleepiness, nausea, reduced food intake, lower limb weakness, and dysuria. Subsequently, his sleepiness significantly deteriorated on July 21st. Five months prior, the patient underwent laparoscopic partial right nephrectomy for clear-cell renal cell carcinoma. Brain MRI revealed abnormal hyperintense lesions in the pontine brain and around the mesencephalic aqueduct on T2 and T2-fluid attenuated inversion recovery (T2-FLAIR) sequences However, these lesions did not exhibit any pathological enhancement. Spinal cord MRI revealed lesions in the C6-C7 and T2-T3 segments on the T2 sequence. His Epworth Sleepiness Scale (ESS) score was 16 (reference range, <10), and 24-hour polysomnography supported the diagnosis of rapid-eye-movement sleep disorder and severe sleep apnea-hypopnea syndrome. Glial fibrillary acidic protein IgG antibodies were detected in the cerebrospinal fluid (1:32, cell-based assay) but not in the serum. The level of hypocretin in the cerebrospinal fluid was 29.92 pg/mL (reference range ≥110 pg/mL), suggesting narcolepsy type 1. After treatment with corticosteroids for This is a provisional file, not the final typeset article approximately 1 month, the patient showed considerable clinical and radiological improvement, as well as an increase in hypocretin levels. Although repeated polysomnography and multiple sleep latency tests suggested narcolepsy, his ESS score decreased to 4. Our findings broaden the range of clinical manifestations associated with GFAP-A, thereby enhancing diagnostic and therapeutic strategies for this disease. Additionally, our results indicate a potential common autoimmune mechanism involving GFAP-A and orexin system dysregulation, warranting further investigation.